A MODERN VIEW OF THE CYLINIC COURSE OF RHEUMATOID ARTHRITIS IN CORONAVIRUS INFECTION - Nargiza Khakimzhanovna Abduazizova; Zafar Abdunaemovich Sharapov (Western European Studies, 2025)
Rheumatoid arthritis (RA) is a rheumatological disease accompanied by joint syndrome, functionally characterized by erosive damage and destruction of joints. The disease occurs predominantly in young and middle-aged individuals and leads to early disability of patients, which in turn determines the social significance and relevance of the problem. COVID-19 infection has caused new features of the course of RA, which determines the medical and social relevance of studying the problem.
Keywords: rheumatoid arthritis; COVID-19 infection; muscle and joint damage